Main Factors Conditioning the Absence of the Final ր and the Origin of the Final ի of the Imperative Singular in Armenian Dialects - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2023)
The 2 sg. Imperative, which was formed in several ways in Old Armenian, has displayed a general tendency toward uniformity in the course of the further development of the Armenian language. In this respect, the strong analogical interaction between the imperative forms of simple verbs of the ե and ի conjugations is especially remarkable. Whereas in some dialects the original distinction between active vs. medio-passive inflection has been preserved, in other dialects simple verbs of the former ե and ի conjugations have coalesced into a single conjugation type partially or fully, whereby either the ending -իր or -է (< Old Arm.-եա՛) of the 2 sg. Imperative has been generalized as a result of analogical extension. Furthermore, on the one hand, the final ր of the Imperative sg. ending -իր has been lost either by phonetic change or by analogy in a number of dialects, and on the other hand, the final vowel -է (going back to the Old Armenian diphthong -եա՛) of the 2 sg. Imperative has undergone further change է>ի in the same dialectal areas. Hence, the final ի of the 2 sg. Imperative in such cases may in principle have resulted either from the phonetic and/or analogical loss of the final ր in the ending -իր or from the phonetic change է>ի. It is not infrequently hard to say unequivocally which of the two aforementioned developments is responsible for the appearance of the form in question. Besides, it is sometimes far from clear whether phonetic change or analogy has entailed the actual disappearance of the final ր in the ending -իր in a particular dialect. In this respect, the retention vs. loss of the final ր in the 2 sg. Imperative of irregular verbs mainly serves as a guideline for revealing the actual cause (namely, articulatory vs. analogical motivation) of the lack of the final ր in the 2 sg. Imperative of regular verbs, though the final ր of the 2 sg. Imperative of some irregular verbs is likely to have been restored secondarily by analogy with the 2 pl. Imperative in a few instances.